Consider the quadratic equation x^2 = 4x-5. How many solutions does the equation have?

A. The equation has one real solution.

B. The equation has two real solutions.

C. The equation has no real solutions.

D. The number of solutions cannot be determined.

5 answers

B. The equation has two real solutions.

To find the solutions to the quadratic equation x^2 = 4x - 5, we can rearrange it to x^2 - 4x + 5 = 0 and then use the quadratic formula:

x = (-b ± √(b^2 - 4ac)) / 2a

In this case, a = 1, b = -4, and c = 5. Plugging in these values, we get:

x = (4 ± √((-4)^2 - 4(1)(5))) / (2(1))
x = (4 ± √(16 - 20)) / 2
x = (4 ± √(-4)) / 2

Since the square root of a negative number is not real, the equation has two complex solutions.
An astronaut drops a rock into a crater on the moon. The distance, d(t), in meters, the rock travels after t seconds can be modeled by the function d(t) = 0.8t^2. What is the average speed, in meters per second, of the rock between 5 and 10 seconds after it was dropped?
To find the average speed of the rock between 5 and 10 seconds, we need to find the total distance the rock traveled during this time and then divide by the total time.

The distance traveled by the rock after 5 seconds:
d(5) = 0.8(5)^2
d(5) = 0.8(25)
d(5) = 20 meters

The distance traveled by the rock after 10 seconds:
d(10) = 0.8(10)^2
d(10) = 0.8(100)
d(10) = 80 meters

So, the total distance traveled between 5 and 10 seconds is:
Total distance = d(10) - d(5)
Total distance = 80 - 20
Total distance = 60 meters

The total time taken is 10 - 5 = 5 seconds.

Average speed = Total distance / Total time
Average speed = 60 meters / 5 seconds
Average speed = 12 meters per second

Therefore, the average speed of the rock between 5 and 10 seconds after it was dropped is 12 meters per second.
What are the roots of the equation x^2+6x-9=0?

A. 3±6√2

B. -3±6√2

C.3±3√2

D.-3±3√2
To find the roots of the equation x^2 + 6x - 9 = 0, we can use the quadratic formula:

x = (-b ± √(b^2 - 4ac)) / 2a

In this case, a = 1, b = 6, and c = -9. Plugging these values into the formula, we get:

x = (-6 ± √(6^2 - 4(1)(-9))) / (2(1))
x = (-6 ± √(36 + 36)) / 2
x = (-6 ± √72) / 2
x = (-6 ± 6√2) / 2
x = -3 ± 3√2

Therefore, the roots of the equation x^2 + 6x - 9 = 0 are:

D. -3 ± 3√2
Similar Questions
  1. consider the equation cos^2x + 4cosx =1a) put the equation in standard quadratic trigonometric equation form. b) use the
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. Consider the following quadratic equation:−y^2−4y−4=0 Step 2 of 2 : Use the discriminant, b2−4ac , to determine the
    1. answers icon 1 answer
  3. nswer the questions about this quadratic equation shown below.(x−3)^2/5=20 (3 points) What should be the first step when
    1. answers icon 1 answer
more similar questions